Pathology and Pathogenesis of Severe Acute Respiratory Syndrome - Gu, Jiang (American Society for Investigative Pathology, 2007)
Severe acute respiratory syndrome (SARS) is an emerging infectious viral disease characterized by severe clinical manifestations of the lower respiratory tract. The pathogenesis of SARS is highly complex, with multiple factors leading to severe injury in the lungs and dissemination of the virus to several other organs. The SARS coronavirus targets the epithelial cells of the respiratory tract, resulting in diffuse alveolar damage. Several organs/cell types may be infected in the course of the illness, including mucosal cells of the intestines, tubular epithelial cells of the kidneys, neurons of the brain, and several types of immune cells, and certain organs may suffer from indirect injury. Extensive studies have provided a basic understanding of the pathogenesis of this disease. In this review we describe the most significant pathological features of SARS, explore the etiological factors causing these pathological changes, and discuss the major pathogenetic mechanisms. The latter include dysregulation of cytokines/chemokines, deficiencies in the innate immune response, direct infection of immune cells, direct viral cytopathic effects, down-regulation of lung protective angiotensin converting enzyme 2, autoimmunity, and genetic factors. It seems that both abnormal immune responses and injury to immune cells may be key factors in the pathogenesis of this new disease.